MALIGNAT LYMPHOMA -DIAGNOSIS, THERAPY AND PROGNOSIS, HODGKIN’S LYMPHOMAS -HODGKIN’S DISEASE, DIFFUSE LAGRGE CELL B LYMPHOMA - DLCBL - Aliu, Zamir; Aliu, Zana (Journal of Morphological Sciences, 2021)
Hodgkin's lymphoma (HL) is a malignant disease of clonal origin from B lymphocytes from the germinal center of the lymph nodes. Many etiologies that are not fully explained, there are risk factors that cause HL disease, the most common of which is the family predisposition, various infections, etc. Hodgkin’s lymphomas are categorized into two main groups according to their specificity and the presence of Reed-Stenberg (RS) cells, neoplastic cells with varying degrees of fibrosis. The diagnosis of LH is confirmed by lymph node biopsy, haemogram, CT of the chest, abdomen, and pelvis, bone marrow biopsy MR, scan, and PET scan.The treatment of HL is done according to protocols using cytostatic to achieve successful therapeutic goals. Diffuse large cell B lymphoma - DGKBL is the most common type of non-Hodgkin lymphoma, occurring in the age group, in the white race in the United States, and equally in both sexes.Characteristically, non-Hodgkin lymphomas are fast-growing tumors with mature B lymphocytes. Diagnostic procedures include blood count, Coombs test, Sedimentation, protein status, electrolyte status, degradation products, LDH, transaminases and liver tests, Flow cytometry. Computerized, PET scan Biopsy and bone marrow aspiration. Keywords : Hodgkin's lymphoma, lymph nodes, disease, non-Hodgkin cells, lymph nodes, growing tumors, diagnostic procedures, lymphomas https://doi.org/10.55302/JMS2142001a